It Takes A Church To Raise A Christian - "Bolsinger, Tod E." (Grand Rapids)
"Revision of the author's thesis (doctoral)--Fuller Theological Seminary, 1991. Includes bibliographical references (p. 175-202) and index."
Keywords: SPIRITUAL LIFE -- CHRISTIANITY.;SPIRITUAL FORMATION